2001
DOI: 10.1053/jlts.2001.23787
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index as a predictor of hepatic steatosis in living liver donors

Abstract: Evaluation of the living donor for liver transplantation is a complex process involving such invasive studies as liver biopsy and angiography. It is important to establish the likelihood and extent of hepatic steatosis in living donors by clinical, imaging, and biochemical parameters to avoid performing a liver biopsy, if possible. In this study, the predictive value of body mass index (BMI), liver chemistry tests, and imaging studies was compared with liver histological examination in 33 potential living dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
184
8
16

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(214 citation statements)
references
References 28 publications
6
184
8
16
Order By: Relevance
“…The BMI is a well-known independent predictor of fat in the liver. 40,41 Regardless of BMI, central adiposity has been shown to be associated with NAFLD in normal weight, obese and diabetic individuals. 17,42,43 As the presence of PHT is related to the degree of steatosis, and as the degree of steatosis is related to the amount of visceral fat, the predictive role of waist circumference can easily be understood.…”
Section: Discussionmentioning
confidence: 99%
“…The BMI is a well-known independent predictor of fat in the liver. 40,41 Regardless of BMI, central adiposity has been shown to be associated with NAFLD in normal weight, obese and diabetic individuals. 17,42,43 As the presence of PHT is related to the degree of steatosis, and as the degree of steatosis is related to the amount of visceral fat, the predictive role of waist circumference can easily be understood.…”
Section: Discussionmentioning
confidence: 99%
“…Overweight and obese patients are higher-risk living liver donors because of greater likelihood of hepatic steatosis and medical problems (diabetes, hypertension, and heart disease), which could increase the postoperative complications. 12,13 However, recent data have shown that selected obese candidates may successfully undergo donation without evidence of increased complications. 14 Accepted donor candidates were more likely to be related to the recipient (including spouses) than rejected candidates.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 144 patients with NASH, BMI was the only independent predictor of the degree of fat infiltration (P = 0.003) 13 and histological examination in 33 potential living liver donors showed that BMI is a strong predictor of hepatic steatosis. 61 However, it has been shown that the abdominal distribution of fat is a predictor of hepatic steatosis, which is independent of body weight and body fat. 62 In a study on 221 biopsy-proven chronic hepatitis C patients, visceral fat distribution rather than BMI proved to be associated with steatosis (P < 0.001).…”
Section: The Association Of Nash With Obesitymentioning
confidence: 99%